Detection of curved text path based on the fuzzy curve-tracing (FCT) algorithm - Hong Yan (6th Document Analysis and Recognition: Proceedings of the International Conference 2001: Seattle, WA, 2001)
Artistic documents often contain text along curved paths. Commonly used computer algorithms for text extraction, which only deal with text along straight lines, cannot be employed to analyze these artistic documents. In this paper, we solve this problem using the fuzzy curve-tracing algorithm. In our method, the character pixels are grouped based on the fuzzy c-means algorithm to reduce the amount of data. Then the cluster centers are connected to form the initial curve representing the text path. Finally the character pixels are clustered again under the constraint that the path must be smooth. Results from several experiments are presented to show the effectiveness of our method.